ANALISIS BIAYA OPERASIONAL DALAM MENINGKATKAN PROFITABILITAS PERUSAHAAN PADA PT. UNITED TRACTORS TBK CABANG PEKANBARU - Karina Silmy Kaffah Helmy Samsuri; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The issue that motivated the creation of this research is present at PT United Tractors Tbk Pekanbaru, where the growth of operational costs incurred by the company is increasing while the growth of profitability is decreasing between 2017 and 2021. This study used a descriptive quantitative approach with primary data from informants from the company and secondary data from corporate financial records from 2017 to 2021. The financial accounts of the company are documented as part of the data collection process. The financial ratio analysis approach is the one that was utilized for the research analysis, specifically for the operational cost analysis using the Operating Efficiency Ratio (OER) and the profitability ratio analysis using the Return On Investment (ROI) ratio. The study's findings indicate that the company's level of operational costs is inefficient, and the results of the calculation of the Return On Investment (ROI) profitability ratio indicate that the company's profitability level is poor because it has frequently fluctuated over the previous five years and has not yet met the standard Return On Investment (ROI) criteria. Keyword: Operational Costs, Profitability